An Electrochemical Sensor based on Electrodeposited CTAB Film on Glassy Carbon Electrode for Detection of Morphine - Abraham, Pinky; Renjini, S.; Anithakumary, V.; Chithra, P.G. (Asian Journal of Chemistry, 2019)
A simple, effective and rapid method for the electrochemical detection of morphine is described based on glassy carbon modified electrode with poly(CTAB). In this work, poly(CTAB) thin film was generated through elecropolymerization of the surfactant CTAB. The formation of nanoporous thin film of poly(CTAB) was confirmed by field emission scanning electron microscopy (FESEM) with energy dispersive spectra (EDS) and Fourier transform infrared spectroscopy (FTIR). The electrochemical behavior of morphine is explained in terms of the anodic oxidation of its tertiary amino group. The limit of detection was calculated as 0.2 μM with a good regression between concentration and peak current of morphine by using differential pulse voltammetry within the range of 50 nM to 20 μM. The poly(CTAB)/GCE based sensor shows excellent electrochemical performance for the detection of morphine and this sensing platform can be effective for the detection of similar molecules.